2009
DOI: 10.1007/s10719-008-9219-4
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational and transcriptional regulation of glycolipid glycosyltransferase genes in apoptotic breast carcinoma cells: VII. Studied by DNA-microarray after treatment with l-PPMP

Abstract: Functions of glycosphingolipids on the eukaryotic cell membranes during the onset of oncogenic processes and cell death are not well understood. Inhibitors of glycosphingolipid biosynthesis were recently found to trigger apoptosis in many carcinoma including breast cancer SKBR-3, MCF-7, and MDA-468 cells through either intrinsic or extrinsic apoptotic pathways as we previously reported. These anti-cancer inhibitors could increase ceramide concentration by blocking functions of glycolipid glycosyltransferases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 41 publications
(76 reference statements)
0
18
0
Order By: Relevance
“…Activation of mitochondria and release of mitochondrial apoptogenic factors by betulinic acid (BA), a melanoma-speci fi c cytotoxic agent in neuroectodermal tumors such as neuroblastoma, medulloblastoma, and Ewing's sarcoma, was fi rst recognized by Fulda and his associates (Li et al 2010b ) . In recent years, we have demonstrated that BA activates the apoptotic pathway via IMCAP in human breast carcinoma cells: SKBR-3, MDA-468, and MCF-7 also (Basu et al 2004b ;Ma et al 2009Ma et al , 2011Kessler et al 2007b ) . Whether these cells also regulate cell surface GSL biosynthesis is not known and is under investigation.…”
Section: Betulin and Betulinic Acid As Apoptotic Agents In Cancer Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Activation of mitochondria and release of mitochondrial apoptogenic factors by betulinic acid (BA), a melanoma-speci fi c cytotoxic agent in neuroectodermal tumors such as neuroblastoma, medulloblastoma, and Ewing's sarcoma, was fi rst recognized by Fulda and his associates (Li et al 2010b ) . In recent years, we have demonstrated that BA activates the apoptotic pathway via IMCAP in human breast carcinoma cells: SKBR-3, MDA-468, and MCF-7 also (Basu et al 2004b ;Ma et al 2009Ma et al , 2011Kessler et al 2007b ) . Whether these cells also regulate cell surface GSL biosynthesis is not known and is under investigation.…”
Section: Betulin and Betulinic Acid As Apoptotic Agents In Cancer Cellsmentioning
confidence: 99%
“…16.4 ) (Basu 1991 ;Basu et al 1999Basu et al , 2000Kaufman et al 1968 ) and LD1a were established before in embryonic chicken brain cells. GD3 ganglioside as a proapoptotic agent has been established in recent years (Ma et al , 2009(Ma et al , 2011Basu et al 2004b ;Kessler et al 2007b ;Malisan and Testi 2002a, b ) . We have employed the disialosyl gangliosides (GD3 and GD1b) to induce apoptosis (Ma et al , 2009(Ma et al , 2011Basu et al 2004b ;Kessler et al 2007b ) in human breast cancer cells, SKBR-3 grown in culture.…”
Section: Disialogangliosidesmentioning
confidence: 99%
See 3 more Smart Citations